Videoconferencing (Polycom) Distance Education - Jennifer L. Gillett-Kaufman; Amanda C. Hodges; R. K. Thomas (EDIS, 2006)
IPM-142, a 4-page fact sheet by J. L. Gillett, A. C. Hodges and R. K. Thomas, provides information to UF/IFAS extension professionals about the advantages of videoconferencing, how to schedule a meeting or training session, and guidelines for facilitators and presenters for better videoconferences, including sample logistics for an in-service training session. Published by the UF Department of Entomology and Nematology, July 2006.